Citrate Anticoagulation for CRRT in Children: Comparison with Heparin. (3rd August 2014) - Fernández, Sara Nicole; Santiago, Maria José; López-Herce, Jesús; García, Miriam; Del Castillo, Jimena; Alcaraz, Andrés José; Bellón, Jose María
Abstract : Regional anticoagulation with citrate is an alternative to heparin in continuous renal replacement therapies, which may prolong circuit lifetime and decrease hemorrhagic complications. A retrospective comparative cohort study based on a prospective observational registry was conducted including critically ill children undergoing CRRT. Efficacy, measured as circuit survival, and secondary effects of heparin and citrate were compared. 12 patients on CRRT with citrate anticoagulation and 24 patients with heparin anticoagulation were analyzed. Median citrate dose was 2.6 mmol/L. Median calcium dose was 0.16 mEq/kg/h. Median heparin dose was 15 UI/kg/h. Median circuit survival was 48 hours with citrate and 31 hours with heparin (P = 0.028 ). 66.6% of patients treated with citrate developed mild metabolic alkalosis, which was directly related to citrate dose. There were no cases of citrate intoxication: median total calcium/ionic calcium index (CaT/I) of 2.16 and a maximum CaT/I of 2.33, without metabolic acidosis. In the citrate group, 45.5% of patients developed hypochloremia and 27.3% hypomagnesemia. In the heparin group, 27.8% developed hypophosphatemia. Three patients were moved from heparin to citrate to control postoperatory bleeding. In conclusion citrate is a safe and effective anticoagulation method for CRRT in children and it achieves longer circuit survival than heparin.